BURGELIJK WETBOEK (Menelusuri Sejarah Hukum Pemberlakuannya di Indonesia) - Erie Hariyanto (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
Burgelijk Wetboek or the book of civil law is historicallyderived from Dutch. It has been applied on the basis ofconcordancy principle; in fact, the legislative institutionhas not published civil laws that being coded and unifiedyet. It is urgent to apply new laws that exclusively managelaw of contract (in particular or general) as a part of civillaws, in order to support the economic activity of nation.Dutch has already revised their own Burgelijk Weboek thathas been applied in Indonesia.